2017
DOI: 10.1177/1541931213601989
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Workload and Stress Measures for Performance Prediction

Abstract: The study of performance, workload, and stress have become a mainstay in the field of Human Factors. These constructs are multi-faceted and are assessed by a variety of measures. In seeking to enhance performance by managing mental workload and stress, it is important for measures to be anchored to meaningful criteria. Workload and stress must be considered with respect to the performance measures that address the most central objectives. While workload and stress research has progressed over the years and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is worthwhile noting that the above three approaches of cognitive load measurement-primary task, subjective perceptions and physiological responses, do not always agree with each other when they are applied concurrently. As has been observed by Hancock et al [245], results from the three approaches could agree with each other (association), or may not correlate (insensitive), or contradict each other (dissociation), with each circumstance commonly being reported in different research studies [262]. For example, Lan et al [58] adopted all three approaches in evaluating the effects of temperature on cognitive load.…”
Section: • Physiological Responsesmentioning
confidence: 92%
“…It is worthwhile noting that the above three approaches of cognitive load measurement-primary task, subjective perceptions and physiological responses, do not always agree with each other when they are applied concurrently. As has been observed by Hancock et al [245], results from the three approaches could agree with each other (association), or may not correlate (insensitive), or contradict each other (dissociation), with each circumstance commonly being reported in different research studies [262]. For example, Lan et al [58] adopted all three approaches in evaluating the effects of temperature on cognitive load.…”
Section: • Physiological Responsesmentioning
confidence: 92%
“…However, in situations in which a higher ecological validity is desired, it is necessary to implement easy-to-use solutions (e.g., [48]) that do not interfere with operator behavior and undermine operational safety. Pioneering works that studied ecologically-valid tasks (e.g., visual display terminal interactions [49]) and more recent studies have confirmed the sensitivity of the theta EEG power spectrum in detecting increased workload levels in operative contexts (e.g., flight simulator [2], military operations simulation facility [50]). Results obtained in driving scenarios are limited and lack consistent results, however [51].…”
Section: Eeg Theta Activity As An Index Of Mental Workloadmentioning
confidence: 95%
“…Furthermore, temporal and occipital θ-activity behaved similarly. Very few studies have focused on those areas as potential indices of mental workload [50,76], but it seems that several cortical areas are related to different processes in the brain while dealing with complex tasks. For example, because off-road navigation performance relies heavily on the visual and motor control systems, it is plausible to explain the changes in temporal and occipital θ-activity if we consider the involvement of these areas in motor and visual processing [77,78].…”
Section: Terrain Complexity Increases Overall θ-Activitymentioning
confidence: 99%